Beyond mindfulness: how Buddhist meditation transforms consciousness through distinct psychological pathways - Wang, Cheng (Frontiers in Psychology, 2025)
Buddhist meditation, encompassing practices such as Samatha (focused attention), Vipassana (open monitoring), and Metta (loving-kindness), offers unique pathways for transforming consciousness beyond conventional mindfulness. In this article, we review the studies that explore how these distinct meditative techniques systematically cultivate meta-cognitive insight, emotional regulation, and self-inquiry, facilitating profound shifts in awareness and personal growth. Recent neuroscience and psychology studies show that these techniques influence the mind in different ways: they strengthen attentional stability, reshape self-referential thinking, and reorganize emotional patterns. Such modifications are evident in reorganized brain networks (for example, the default-mode network) and in characteristic EEG patterns. While sharing some parallels with Western mindfulness and hypnosis, Buddhist meditation uniquely emphasizes ethical integration and profound introspection. Challenges remain in objectively measuring advanced meditative states, particularly the experience of “no-self” (anattā), due to the reliance on subjective self-report. Future research should incorporate culturally sensitive methodologies, objective behavioral tasks, and interdisciplinary approaches like neurophenomenology to integrate traditional contemplative wisdom with rigorous scientific inquiry.